2009
DOI: 10.1063/1.3225998
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency p-i-n top-emitting organic light-emitting diodes with a nearly Lambertian emission pattern

Abstract: We report high efficiency phosphorescent green p-i-n top-emitting organic light-emitting diodes consisting of metal anodes (Ag and Al), a rhenium oxide p-dopant, a rubidium carbonate n-dopant, and a semitransparent Ag cathode. Significantly high peak current efficiencies of 88 and 73 cd/A are demonstrated for the devices using Ag and Al anodes, respectively, through the optimization of organic layer thickness. The electroluminescence intensities of the Ag-based device with viewing angles show a nearly Lamberti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 23 publications
(20 reference statements)
1
8
0
Order By: Relevance
“…1,2 In contrast to inorganic semiconductors, however, the charge generation efficiencies defined as the ratio of carrier density to the number of dopant molecules is low in organic semiconductors, requiring high doping concentration for device applications. [3][4][5][6][7][8] Such high doping concentration limits the application of doping technology in organic semiconductors because the diffusion of dopants can destabilize organic electronic devices. 9,10 In previous papers, we reported that a diverse range of charge generation efficiencies were obtained for various combinations of p-dopants and hosts.…”
Section: Homogeneous Dispersion Of Organic P-dopants In An Organic Sementioning
confidence: 99%
See 1 more Smart Citation
“…1,2 In contrast to inorganic semiconductors, however, the charge generation efficiencies defined as the ratio of carrier density to the number of dopant molecules is low in organic semiconductors, requiring high doping concentration for device applications. [3][4][5][6][7][8] Such high doping concentration limits the application of doping technology in organic semiconductors because the diffusion of dopants can destabilize organic electronic devices. 9,10 In previous papers, we reported that a diverse range of charge generation efficiencies were obtained for various combinations of p-dopants and hosts.…”
Section: Homogeneous Dispersion Of Organic P-dopants In An Organic Sementioning
confidence: 99%
“…6,7 The charge generation efficiencies of p-dopants depended on the energy difference between the highest occupied molecular orbital ͑HOMO͒ level of the hosts and the lowest unoccupied molecular orbital ͑LUMO͒ level of the dopant ͑⌬E = E HOMO,host − E LUMO,dopant ͒. 5,6 The nanoclusters formation of rhenium oxide ͑ReO 3 ͒ and molybdenum oxide ͑MoO 3 ͒ dopants was verified as an origin of low charge generation efficiency in organic semiconductors through the transmission electron microscopy ͑TEM͒ analysis. The charge generation efficiencies of metal oxide dopants still remained very low in the range of 0.3%-4%.…”
Section: Homogeneous Dispersion Of Organic P-dopants In An Organic Sementioning
confidence: 99%
“…In recent years there have been many reports of glass-based top-emissive OLEDs with good performance where Ag, 7,8 Al/Ag, 9,10 LiF/Al 12 and LiF/Al/Ag [12][13][14][15][16] have been applied as the transparent cathode, often in combination with a capping layer such as N,N'-bis(naphthalen-1-yl)-N,N'-bis(phenyl)-benzidine (NPB), [10][11][12][13][14][15][16][17] N,N,N',N'-tetrakis(4-methoxyphenyl)benzidine (MeO-TPD), 9 tris(8-hydroxyquinolinato)aluminium (AlQ3) 3 , 17,18 tin-doped indium oxide (ITO), SiO 2 , 15 or ZnSe. 16,19 With this second metal electrode, a microcavity resonator is obtained that amplifies a specific wavelength range and particular emission angles 15,20,21 (acting like a Fabry-Pérot filter).…”
Section: Top-emissive Oleds On Metal Foilmentioning
confidence: 99%
“…5 Thus, the experimental efficiency values are obtained by integration of spectral and angular resolved measurements, 6 performed with a calibrated self-made spectrogoniometer.…”
mentioning
confidence: 99%